Peroxisome Proliferator-Activated Receptor-𝛾 Is a Potent Target for Prevention and Treatment in Human Prostate and Testicular Cancer - Masahide Matsuyama; Rikio Yoshimura (PPAR Research)
Peroxisome proliferator-activated receptor-𝛾 (PPAR)-𝛾 is a ligand-activated transcriptional factor belonging to steroid receptor superfamily. PPAR-𝛾 plays a role in both adipocyte differentiation and tumorigenesis. Up to date, PPAR-𝛾 is expressed in various cancer tissues, and PPAR-𝛾 ligand induces growth arrest of these cancer cells. In this study, we examined the expression of PPAR-𝛾 in prostate cancer (PC) and testicular cancer (TC) by RT-PCR and immunohistochemistry, and we also examined the effect of PPAR-𝛾 ligand in these cells by MTT assay, hoechest staining, and flow cytometry. PPAR-𝛾 expression was significantly more extensive and intense in malignant tissues than in normal tissues. PPAR-𝛾 ligand induced the reduction of malignant cell viability through apoptosis. These results demonstrated that the generated PPAR-𝛾 in PC and TC cells might play an important role in the tumorigenesis. PPAR-𝛾 may become a new target in the treatment of PC and TC.